Threads and reused textiles as decorative items in Deir el-Medina, Egypt - Spinazzi-Lucchesi, Chiara (Archaeological Textiles Review, 2022)
Yarns and textiles can be used and reused for multiple purposes other than as clothing and household furnishing. In this paper, four different objects from the village of Deir el-Medina (Egypt) are examined. Some of them were purposely made, while others were reused strips of textiles. All of them share an evident trait, which is their decorative function. Through a detailed analysis of these unusual artefacts, it will be possible to shed light on some little known aspects of ornaments in Deir el-Medina.